1983
DOI: 10.1161/01.hyp.5.5.682
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Na+,K+-ATPase activity and [3H]ouabain binding sites in sarcolemma prepared from hearts of spontaneously hypertensive rats.

Abstract: SUMMARY Na+ ,K+-ATPase activity, phosphorylation, and [ 3 H]ouabain binding in sarcolemma isolated from spontaneously hypertensive rat (SHR) hearts were compared to the same parameters in sarcolemma from normotensive rat (WKY) hearts. Sarcolemma prepared from SHR heart contained significantly less ouabain-inhibitable ATPase activity than sarcolemma from WKY heart. No significant differences in sarcolemmal protein content or recovery were noted between the two groups. The numbers of phosphorylation sites and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Other Na + transport pathways are altered in kidney cells from SHR that in turn might affect the Na + gradient across the brush-border membranes. Thus, Na + -H + exchange was stimulated in the kidney cortex from SHR [5], and as previously reported in several tissues from SHR [7,[24][25][26] and in patients with essential hypertension [27], we found a decrease in the Na + -K + -ATPase activity in kidney homogenates prepared from SHR when compared to WKY rats. In conclusion, we have found a decrease in the transport of D-glucose and D-galactose in renal BBMVs prepared from SHR which paralleled a reduction in the density of Na + -dependent sugar cotransporters, as well as changes in the Na + gradient across the brush-border membrane.…”
Section: Research Articlesupporting
confidence: 90%
“…Other Na + transport pathways are altered in kidney cells from SHR that in turn might affect the Na + gradient across the brush-border membranes. Thus, Na + -H + exchange was stimulated in the kidney cortex from SHR [5], and as previously reported in several tissues from SHR [7,[24][25][26] and in patients with essential hypertension [27], we found a decrease in the Na + -K + -ATPase activity in kidney homogenates prepared from SHR when compared to WKY rats. In conclusion, we have found a decrease in the transport of D-glucose and D-galactose in renal BBMVs prepared from SHR which paralleled a reduction in the density of Na + -dependent sugar cotransporters, as well as changes in the Na + gradient across the brush-border membrane.…”
Section: Research Articlesupporting
confidence: 90%
“…30, 31 At a cellular level there is decreased density of sodium and potassium pumps, which leads to decreased intracellular potassium concentrations and prolongs repolarization. 32 Along these lines, cellular studies have shown that ATP sensitive potassium channels are more likely to be open during ischemia in hypertrophied myocytes compared to normal myocytes. 33 This can prolong repolarization and the QT interval, allowing for after-depolarizations and triggered activity that initiates ventricular arrhythmias.…”
Section: Mechanisms Of Ventricular Arrhythmogenesis In Lvhmentioning
confidence: 99%
“…In several studies performed on other models of cardiac hypertrophy e.g. spontaneously hypertensive rats (Lee et al 1983) or one-kidney, one-clip hypertensive rats (Clough et al 1983) a reduced activity of Na + /K + -ATPase was found. Additionally, Tepel et al (1994) found an increased cytosolic sodium and a reduced Na + /K + -ATPase activity in lymphocytes and erythrocytes of TGR.…”
Section: Discussionmentioning
confidence: 99%